Indoor thermal environment in kindergarten at Seri Iskandar, Perak / Nur Syafiqah Zamri and Nazhatulzalkis Jamaluddin - Zamri, Nur Syafiqah; Jamaluddin, Nazhatulzalkis (2023)
Indoor thermal comfort is crucial for well-being and productivity, especially in educational settings like kindergartens. This study examines thermal conditions and occupant satisfaction in such environments. The American Society of Heating, Refrigerating, and Air Conditioning Engineers (ASHRAE) defines thermal comfort as occupants' contentment with their surroundings, yet achieving universal comfort is complex due to individual differences. Adaptive models, especially in naturally conditioned spaces, highlight the interplay between individuals and their environment. Focused on kindergartens, where classroom quality directly affects comfort, this research aims to grasp user perceptions, assess occupant satisfaction, and explore thermal conditions. The indoor thermal environment's intricacy arises from temperature, humidity, air circulation, and sunlight. While global benchmarks provide thermal guidance, personal preferences, and adaptability are crucial. Findings from two kindergarten case studies showcase diverse comfort levels among staff, underscoring the need to address individual preferences. Recommendations include enhanced air circulation, precise temperature regulation, insulation, sunlight management, personalized settings, weather-adaptive strategies, and ongoing assessment. This study underscores thermal comfort's importance in educational settings, promoting well-being and enriched learning experiences through the suggested measures.